PENERAPAN MODEL PEMBELAJARAN ACCELERATED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS X SMAN 14 PEKANBARU - Cahya, Anggra Prasetya; Rery, H. R. Usman; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The application of Accelerated Learning model aims to improve student achievement on subject of Atomic Structure and Periodic System Elements in class X SMAN 14 Pekanbaru. This type of research is experimental research design with randomized control group pretest-posttest. Samples were students in class X2 as an experimental class and students in class X1 as a control class. Data analysis technique used is the t test. The test results of data analysis obtained t calculated > t table is 3.91> 1.67, meaning that the application of Accelerated Learning model can improve student achievement on subject of Atomic Structure and Periodic System Elements in class X SMAN 14 Pekanbaru with the influence coefficient of 17, 74%.Keywords : Accelerated Learning, Learning Achievement, Atomic Structure and Periodic System Elements